2008
DOI: 10.1111/j.1365-2028.2007.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates with the distribution and abundance of endangered Sclater’s monkeys (Cercopithecus sclateri) in southern Nigeria

Abstract: A distribution survey of the endangered Sclater's monkey (Cercopithecus sclateri) was conducted over a wide area in southern Nigeria using forest surveys and hunter interviews. Sclater's monkey, Nigeria's only endemic primate species, is restricted to a land area of about 28,500 km 2 in the densely human-populated, oil-producing region of southern Nigeria. Results indicate that this species is not as rare as previously thought; we confirmed its presence in 27 formerly unknown sites. Based on encounter-rate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Concerning primates, wild populations of C. sclateri were discovered just in the late 1980s (whereas this species was described from captive/museum specimens in the early 20th Century) and were considered extremely rare and critically endangered till the end of the 1990s (e.g., Oates and Anadu 1988;Oates et al 1992;Tooze 1995). However, it has now been discovered in several places across the region (Baker and Olubode 2008;Baker et al 2009), and certainly it is doing well even in altered forest sites provided that it is not hunted by people (Baker and Olubode 2008;Baker et al 2009;Oates 2011;John Oates and Lynne Baker, personal communication to 14 F. Petrozzi et al LL). Considering that: (1) the Niger Delta region has traditionally been actively surveyed by expert primatologists since the 1960s (e.g., Oates 1999Oates , 2011, and (2) the species was never observed either alive or in bushmeat markets until the 1980s by scientists or naturalists (whereas captive specimens and skins came to Europe from Nigeria) (John Oates, personal communication to LL), we consider unlikely that C. sclateri escaped the attention of such dedicated surveys.…”
Section: Range/niche Shifting and The Dynamics Of Animal Populations mentioning
confidence: 91%
See 1 more Smart Citation
“…Concerning primates, wild populations of C. sclateri were discovered just in the late 1980s (whereas this species was described from captive/museum specimens in the early 20th Century) and were considered extremely rare and critically endangered till the end of the 1990s (e.g., Oates and Anadu 1988;Oates et al 1992;Tooze 1995). However, it has now been discovered in several places across the region (Baker and Olubode 2008;Baker et al 2009), and certainly it is doing well even in altered forest sites provided that it is not hunted by people (Baker and Olubode 2008;Baker et al 2009;Oates 2011;John Oates and Lynne Baker, personal communication to 14 F. Petrozzi et al LL). Considering that: (1) the Niger Delta region has traditionally been actively surveyed by expert primatologists since the 1960s (e.g., Oates 1999Oates , 2011, and (2) the species was never observed either alive or in bushmeat markets until the 1980s by scientists or naturalists (whereas captive specimens and skins came to Europe from Nigeria) (John Oates, personal communication to LL), we consider unlikely that C. sclateri escaped the attention of such dedicated surveys.…”
Section: Range/niche Shifting and The Dynamics Of Animal Populations mentioning
confidence: 91%
“…Although we acknowledge that this Abundance Index does not have full scientific support (Akani, Aifesehi, et al 2015), yet it may give a preliminary indication of the relative abundance of the various species for a region of tropical Africa where there is no data available on the population abundance of any mammal species apart from primates (e.g. Baker and Olubode 2008;Baker et al 2009).…”
Section: Statistical Analysesmentioning
confidence: 98%
“…Primates ranked very high in the list of threatened species with 6 species being red-listed, but there was also one carnivore (Genetta cristata), two pangolins (Manis tricuspis and Uromanis tetradactyla), one sirenid (Trichecus senegalensis), and the already mentioned elephant Loxodonta cyclotis and hippo Hippopotamus amphibius. Unfortunately, apart from a few primates (e.g., Baker and Olubode 2008;Baker et al 2009), there are no data available on the demography and ecology of these threatened species in the Niger Delta.…”
Section: Iucn Red-listing Of Niger Delta Mammalsmentioning
confidence: 98%
“…Literature entries reporting precise locality data, recorded in 2005-2015, were also used (e.g., Baker and Olubode 2008;Baker et al 2009;Pimley 2009; Colyn et al Ikemeh 2007aIkemeh , b, 2013Akani et al 2014aAkani et al , b, c, 2015Petrozzi et al 2015). Although published after 2005, Blench (2007) was not considered as a source for current data (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) because (1) most of this author's records came from Powell (1993), and (2) Blench did not explicitly distinguish between his own original/recent records and those drawn from Powell (1993).…”
Section: Protocolmentioning
confidence: 99%
“…Kassali et al [10] observed that farmers often walk approximately 6km a day to their farms, perhaps due to population pressure, land tenure system or availability of fertile soils close to the settlements [12]. Fishing is a major activity supplying more than 80% of animal protein [13,14], as a result, most communities are classified as fishing hamlets established to take advantage of fishing opportunities presented by the riverine ecosystem [15].…”
Section: Land Use Activitiesmentioning
confidence: 99%